Body perception and physical activity level in undergraduate nutrition and dietetics students. (Revista horizonte, 2014)
Body image perception has shown a high relation to health from a physical and emotional perspective, as well with levels of physical activity in some populations. This research aims to determine the perception of body image and physical activity level in nutrition's freshmen students. The study has an transversal-descriptive design, was developed with 35 individuals (n=35) who were selected through a purposive sample. As data collection instruments have been used two test: (a) Body Shape Quiestionnaire (BSQ) to assess satisfaction and customer perception of body image, and (b) IPAQ questionnaire, which assesses the level of physical activity. The study results state that 65,7% of the individuals are not concerned for his/her body shape, and the 51,43% of the sample has a high level of physical activity.